The impacts of game farming on worker's livelihoods: a case of a private game reserve in South Africa's Eastern Cape Province - Ngcoza, Nkosiphendule Mbasa (Rhodes University, Faculty of Humanities, Department of Sociology)
Land use shifts from commercial agricultural farming to game farming through wildlife tourism, has been prevalent in post-apartheid South Africa. Scholars have argued that wildlife tourism to be more profitable than other forms of commercial farming. As such, game farming has been promoted as a community-engaged vehicle for rural development through the creation of better employment opportunities. This study explored the implications of these shifts on the livelihoods of farm workers living on the game farms. Unlike labour tenants, farm workers who live on the private game, earn a wage. However, farm workers' accommodation on the game farm is dependent on them being employed on the farm. The aim of the study was to explore the impacts of game farms on the livelihoods of farm workers since the shift from commercial agricultural practices to tourism services in the form of private game reserves. A case study research design was used to gather in-depth information about the multiple realities of the participants, not only about their employment relationships, but also their experiences living on the property on which they are employed. I collected data mainly through semi-structured interviews. I also collected and analysed company documents. The study adopted a Sustainable Livelihoods Framework as a theoretical schema to analyse the livelihood assets readily available to the farm dwellers and the various livelihood strategies they used to make ends meet. The findings of the study revealed that residing on the game farm, although it provided access to free accommodation, tended to pose several challenges to the workers, including i) exploitative employment structures and ii) insecure land rights. The findings also revealed human capital development initiatives mandated for employees were not formally documented. As a result, employees were confined in their current employment. Consequently, the study revealed that participants who had been employed by the game farm for over a decade showed little evidence of enhanced livelihoods. The livelihood strategies of the participants were their basic employment wage, the use of money borrowing systems through stokvels, and informal trading such as selling sweets and chips in the game reserve villages where other workers live with their families.
Keywords: Game reserves -- South Africa; Land use -- South Africa; Agriculture Economic aspects -- South Africa; Wildlife tourism; Rural development -- South Africa; Rural development Sociological aspects